Model Works During the Cultural Revolution - Zhang, Qingyan (Asian Studies E-Books Online, Collection 2026., 2026)
This book offers a groundbreaking exploration of China's Cultural Revolution through the lens of the Model Works, revealing their intricate fusion of politics, art, and ideology. From Mao's diplomatic maneuvers to the enduring legacy of revolutionary opera, it traces how artistic innovation became a vehicle for cultural transformation and global strategy. Rich in historical detail, it illuminates the creative genius of figures like Yu Huiyong, the political theater of Jiang Qing, and the post-revolution commodification of socialist culture. Both a cultural history and a meditation on revolution's unfinished mission, it challenges readers to rethink the intersections of arts and politics.